High-transparency and low-haze polyethylene composite material as well as preparation method and application thereof
By adding a specific proportion of composite nucleating agent microemulsion to the polyethylene film, the problems of low transparency and haze of traditional polyethylene film materials are solved, and the preparation of high-transparent and low haze of polyethylene composite materials is realized, which has enhanced its application potential in high-end fields.
Patent Information
- Application Number
- CN202411876395.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional polyethylene film materials have significant problems in transparency and haze, resulting in limited applications in high-end fields.
By adding composite nucleating agent microemulsion to linear low-density polyethylene (LLDPE), specifically, sodium benzoate, lithium difluorosulfonimide and fluorinated polyester nonionic surfactant in a specific proportion to form a microemulsion, and processing it through high-speed mixing and twin-screw extruder, a highly transparent and low haze polyethylene composite material is prepared.
The transparency of the polyethylene film is significantly improved to >96%, and the haze is reduced to <5%, while maintaining the processing performance and cost-effectiveness of the film.
Smart Images

Figure BDA0005196988730000121 
Figure BDA0005196988730000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyethylene, and in particular relates to a high-transparency, low-haze polyethylene composite material and a preparation method and application thereof. Background Art
[0002] As an important component of the plastic packaging field, polyethylene (PE) film materials are widely used in food packaging, agricultural covering, building waterproofing, electronic appliances and other industries due to their advantages such as light weight, chemical corrosion resistance, easy processing and high cost-effectiveness. However, traditional polyethylene film materials have significant problems in transparency and haze, which limits their application in some high-end fields.
[0003] Traditional polyethylene films often have low transparency due to the influence of molecular structure, crystallinity and additives. Transparency is a key indicator to measure the ability of a material to transmit light. For food packaging, low transparency not only affects the visual display of the product, but may also cause the food inside the package to deteriorate faster due to insufficient light penetration, affecting food safety and shelf life. In addition, in the field of electronics and electrical appliances, low-transparency films limit light transmission, affecting the brightness and uniformity of LED lighting products, as well as the clarity of display devices.
[0004] Haze refers to the phenomenon of light scattering caused by tiny particles, uneven crystallization or precipitation of additives when light passes through a material, which manifests as a blurry or hazy effect on the surface of the material. High haze not only reduces the visual effect of the material, but also may affect the utilization rate of light and cause energy waste. In the field of food packaging, high haze film will make it difficult for consumers to intuitively judge the freshness and color of the food in the package, affecting their willingness to buy. In the manufacture of optical components, high haze directly reduces the light transmittance of the product, affecting the imaging quality and visual experience.
[0005] Therefore, in view of the adverse effects of low transparency and high haze of traditional polyethylene film materials, developing a new composite material that can maintain the original processing performance and cost-effectiveness of polyethylene while significantly improving transparency and reducing haze has become a technical problem that the current industry urgently needs to solve. The present invention aims to solve the above problems and provide a polyethylene composite material with high transparency and low haze, and a preparation method and application thereof. Summary of the invention
[0006] In view of the defects of the above-mentioned prior art, an object of the present invention is to provide a polyethylene composite material with high transparency and low haze, aiming to solve the technical problems of low transparency and high haze of the existing polyethylene composite materials.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A highly transparent, low-fog polyethylene composite material, comprising the following components in parts by weight:
[0009] Linear low density polyethylene LLDPE 100 parts
[0010] Composite nucleating agent microemulsion 0.05-0.5 parts
[0011] Antioxidant 0.1-0.3 parts
[0012] Lubricant 0.1-0.5 parts.
[0013] The antioxidant is selected from one or more of antioxidant 1010, antioxidant 168 or antioxidant 1076;
[0014] The lubricant is one or more of zinc stearate, calcium stearate or magnesium stearate;
[0015] The composite nucleating agent microemulsion is a microemulsion obtained by compounding sodium benzoate and lithium bis(fluorosulfonyl)imide LiFSI;
[0016] The preparation method of the composite nucleating agent microemulsion is:
[0017] Sodium benzoate and lithium bis(fluorosulfonyl)imide are dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution, a certain amount of surfactant is added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly, then the sodium benzoate aqueous solution is added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 30-50 seconds, and stirred and emulsified to obtain a composite nucleating agent microemulsion.
[0018] Wherein, the surfactant is a fluorinated polyester nonionic surfactant;
[0019] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is (3-5):1:(0.2-0.5);
[0020] The mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10-20%;
[0021] The mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5-15%.
[0022] The second object of the present invention is to provide a method for preparing a high-transparency, low-haze polyethylene composite material, comprising the following steps:
[0023] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 10-15 minutes;
[0024] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed and extruded at 160-220° C. to form granules to obtain a highly transparent and low-haze polyethylene composite material.
[0025] The third object of the present invention is to provide a highly transparent, low-haze polyethylene film, which is prepared from the above-mentioned polyethylene composite material. The specific preparation method is as follows: the polyethylene composite material is added to an extruder at 160-220°C, and after extrusion casting, a transparent, low-haze polyethylene film with a thickness of 30-50μm is obtained.
[0026] The polyethylene film has a transparency greater than 96%, a haze less than 5%, and a fisheye less than 1.
[0027] The fourth object of the present invention is to provide an application of a polyethylene composite material in improving the transparency and haze of polyethylene films.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] (1) The inventors creatively add a composite nucleating agent microemulsion of a specific composition to an LLDPE matrix resin in a polyethylene composite material, and add sodium benzoate, lithium bis(fluorosulfonyl)imide and a specific surfactant, a fluorinated polyester nonionic surfactant, to the composite nucleating agent microemulsion. On the one hand, the microemulsion process is used to improve the dispersion performance of the composite nucleating agent. On the other hand, by selecting a specific type of composite nucleating agent, a heterogeneous nucleation effect is played in the preparation process of the polyethylene film, the nucleation points are increased, the transparency of the polyethylene film is improved and the haze is reduced. The polyethylene film finally obtained has excellent properties, reaching a transparency of more than 96%, a haze of less than 5%, and a film fisheye of less than 1.
[0030] (2) The inventors have also creatively discovered that when sodium benzoate, lithium bis(fluorosulfonyl)imide and a specific surfactant, a fluorinated polyester nonionic surfactant, are in a specific ratio in the composite nucleating agent microemulsion, the three play a synergistic role. By controlling the process parameters for preparing the microemulsion at the same time, the properties of the obtained polyethylene film are optimized. DETAILED DESCRIPTION
[0031] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0032] Unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art. However, if there is any conflict, the definitions in this specification shall prevail.
[0033] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0034] The raw materials are selected as follows:
[0035] LLDPE: ZF4523 of Sinopec Zhenhai Refining;
[0036] Antioxidant: Antioxidant 1010;
[0037] Lubricant: calcium stearate;
[0038] Surfactant: FC4430 from 3M Company.
[0039] Preparation Example 1
[0040] Preparation of composite nucleating agent microemulsion R-1:
[0041] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0042] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 4:1:0.2; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0043] Preparation Example 2
[0044] Preparation of composite nucleating agent microemulsion R-2:
[0045] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0046] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 4:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0047] Preparation Example 3
[0048] Preparation of composite nucleating agent microemulsion R-3:
[0049] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0050] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 3:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0051] Preparation Example 4
[0052] Preparation of composite nucleating agent microemulsion R-4:
[0053] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0054] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 5:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0055] Comparative Preparation Example 1
[0056] Preparation of composite nucleating agent microemulsion CR-1:
[0057] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0058] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 2:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0059] Comparative Preparation Example 2
[0060] Preparation of composite nucleating agent microemulsion CR-2:
[0061] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0062] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 6:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0063] Comparative Preparation Example 3
[0064] Preparation of composite nucleating agent microemulsion CR-3:
[0065] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0066] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 4:1:0.1; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0067] Comparative Preparation Example 4
[0068] Preparation of composite nucleating agent microemulsion CR-4:
[0069] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0070] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 4:1:0.6; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0071] Comparative Preparation Example 5
[0072] Preparation of composite nucleating agent microemulsion CR-5:
[0073] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 20 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0074] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 4:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0075] Comparative Preparation Example 6
[0076] Preparation of composite nucleating agent microemulsion CR-6:
[0077] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant FC4430 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 60 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0078] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 4:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0079] Comparative Preparation Example 7
[0080] Preparation of composite nucleating agent microemulsion CR-7:
[0081] Sodium benzoate and lithium bis(fluorosulfonyl)imide were dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution. A certain amount of surfactant Tween 80 was added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly. Then, the sodium benzoate aqueous solution was added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 50 seconds, and the mixture was stirred and emulsified for 30 minutes to obtain a composite nucleating agent microemulsion.
[0082] The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is 4:1:0.5; the mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10%; and the mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5%.
[0083] Example 1
[0084] A polyethylene composite material, comprising the following components in parts by weight:
[0085] Linear low density polyethylene LLDPE 100 parts
[0086] Composite nucleating agent microemulsion R-10.05 parts
[0087] Antioxidant 10100.3 parts
[0088] 0.3 parts of calcium stearate.
[0089] The method for preparing the polyethylene composite material comprises the following steps:
[0090] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0091] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0092] Example 2
[0093] A polyethylene composite material, comprising the following components in parts by weight:
[0094] Linear low density polyethylene LLDPE 100 parts
[0095] Composite nucleating agent microemulsion R-20.05 parts
[0096] Antioxidant 10100.3 parts
[0097] 0.3 parts of calcium stearate.
[0098] The method for preparing the polyethylene composite material comprises the following steps:
[0099] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0100] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0101] Example 3
[0102] A polyethylene composite material, comprising the following components in parts by weight:
[0103] Linear low density polyethylene LLDPE 100 parts
[0104] Composite nucleating agent microemulsion R-30.05 parts
[0105] Antioxidant 10100.3 parts
[0106] 0.3 parts of calcium stearate.
[0107] The method for preparing the polyethylene composite material comprises the following steps:
[0108] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0109] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0110] Example 4
[0111] A polyethylene composite material, comprising the following components in parts by weight:
[0112] Linear low density polyethylene LLDPE 100 parts
[0113] Composite nucleating agent microemulsion R-40.05 parts
[0114] Antioxidant 10100.3 parts
[0115] 0.3 parts of calcium stearate.
[0116] The method for preparing the polyethylene composite material comprises the following steps:
[0117] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0118] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0119] Example 5
[0120] A polyethylene composite material, comprising the following components in parts by weight:
[0121] Linear low density polyethylene LLDPE 100 parts
[0122] Composite nucleating agent microemulsion R-20.1 parts
[0123] Antioxidant 10100.3 parts
[0124] 0.3 parts of calcium stearate.
[0125] The method for preparing the polyethylene composite material comprises the following steps:
[0126] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0127] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0128] Comparative Example 1
[0129] A polyethylene composite material, comprising the following components in parts by weight:
[0130] Linear low density polyethylene LLDPE 100 parts
[0131] Composite nucleating agent microemulsion CR-10.05 parts
[0132] Antioxidant 10100.3 parts
[0133] 0.3 parts of calcium stearate.
[0134] The method for preparing the polyethylene composite material comprises the following steps:
[0135] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0136] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0137] Comparative Example 2
[0138] A polyethylene composite material, comprising the following components in parts by weight:
[0139] Linear low density polyethylene LLDPE 100 parts
[0140] Composite nucleating agent microemulsion CR-20.05 parts
[0141] Antioxidant 10100.3 parts
[0142] 0.3 parts of calcium stearate.
[0143] The method for preparing the polyethylene composite material comprises the following steps:
[0144] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0145] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0146] Comparative Example 3
[0147] A polyethylene composite material, comprising the following components in parts by weight:
[0148] Linear low density polyethylene LLDPE 100 parts
[0149] Composite nucleating agent microemulsion CR-30.05 parts
[0150] Antioxidant 10100.3 parts
[0151] 0.3 parts of calcium stearate.
[0152] The method for preparing the polyethylene composite material comprises the following steps:
[0153] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0154] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0155] Comparative Example 4
[0156] A polyethylene composite material, comprising the following components in parts by weight:
[0157] Linear low density polyethylene LLDPE 100 parts
[0158] Composite nucleating agent microemulsion CR-4 0.05 parts
[0159] Antioxidant 10100.3 parts
[0160] 0.3 parts of calcium stearate.
[0161] The method for preparing the polyethylene composite material comprises the following steps:
[0162] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0163] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0164] Comparative Example 5
[0165] A polyethylene composite material, comprising the following components in parts by weight:
[0166] Linear low density polyethylene LLDPE 100 parts
[0167] Composite nucleating agent microemulsion CR-5 0.05 parts
[0168] Antioxidant 10100.3 parts
[0169] 0.3 parts of calcium stearate.
[0170] The method for preparing the polyethylene composite material comprises the following steps:
[0171] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0172] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0173] Comparative Example 6
[0174] A polyethylene composite material, comprising the following components in parts by weight:
[0175] Linear low density polyethylene LLDPE 100 parts
[0176] Composite nucleating agent microemulsion CR-6 0.05 parts
[0177] Antioxidant 10100.3 parts
[0178] 0.3 parts of calcium stearate.
[0179] The method for preparing the polyethylene composite material comprises the following steps:
[0180] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0181] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0182] Comparative Example 7
[0183] A polyethylene composite material, comprising the following components in parts by weight:
[0184] Linear low density polyethylene LLDPE 100 parts
[0185] Composite nucleating agent microemulsion CR-7 0.05 parts
[0186] Antioxidant 10100.3 parts
[0187] 0.3 parts of calcium stearate.
[0188] The method for preparing the polyethylene composite material comprises the following steps:
[0189] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0190] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0191] Comparative Example 8
[0192] A polyethylene composite material, comprising the following components in parts by weight:
[0193] Linear low density polyethylene LLDPE 100 parts
[0194] Sodium benzoate 0.05 parts
[0195] Antioxidant 10100.3 parts
[0196] 0.3 parts of calcium stearate.
[0197] The method for preparing the polyethylene composite material comprises the following steps:
[0198] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0199] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0200] Comparative Example 9
[0201] A polyethylene composite material, comprising the following components in parts by weight:
[0202] Linear low density polyethylene LLDPE 100 parts
[0203] Lithium bis(fluorosulfonyl)imide 0.05 parts
[0204] Antioxidant 10100.3 parts
[0205] 0.3 parts of calcium stearate.
[0206] The method for preparing the polyethylene composite material comprises the following steps:
[0207] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0208] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0209] Comparative Example 10
[0210] A polyethylene composite material, comprising the following components in parts by weight:
[0211] Linear low density polyethylene LLDPE 100 parts
[0212] Sodium benzoate 0.04 parts
[0213] Lithium bis(fluorosulfonyl)imide 0.01 parts
[0214] Antioxidant 10100.3 parts
[0215] 0.3 parts of calcium stearate.
[0216] The method for preparing the polyethylene composite material comprises the following steps:
[0217] (1) Weigh the raw materials of each component according to the formula, add them into a high-speed mixer, and mix at high speed for 15 minutes;
[0218] (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed, extruded and granulated at 160-220° C. to obtain a polyethylene composite material.
[0219] Polyethylene film sample preparation:
[0220] The polyethylene composite materials of Examples 1-5 and Comparative Examples 1-10 were added into an extruder at 160-220° C., and polyethylene films with a thickness of 30 μm were prepared after extrusion casting.
[0221] Polyethylene film performance test:
[0222] Transparency and haze: tested according to GB / T 2410--2008;
[0223] Appearance performance: characterized by thin film fisheye;
[0224] The performance results are shown in Table 1-Table 2.
[0225] Table 1
[0226]
[0227] Table 2
[0228]
[0229] By comparing Examples 1-5 in Table 1 with Comparative Examples 1-10 in Table 2, it can be seen that the polyethylene composite material of the present invention achieves a synergistic effect by adding a composite nucleating agent microemulsion of a specific composition to LLDPE, and by adding a specific proportion of sodium benzoate, lithium bis(fluorosulfonyl)imide and a specific surfactant to the composite nucleating agent microemulsion. At the same time, the process parameters for preparing the microemulsion are controlled, and the polyethylene film finally obtained has the best performance, with transparency >96%, haze <5%, and the best performance in Example 2.
[0230] By comparing Examples 1-5 with Comparative Examples 1-4, it can be seen that in the preparation process of the composite nucleating agent microemulsion in the polyethylene composite material of the present invention, sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant FC4430 play a synergistic role in a specific proportion, and together bring about improvements in the transparency, haze and appearance performance of the polyethylene film.
[0231] By comparing Examples 1-5 with Comparative Examples 5-6, it can be seen that the performance of the polyethylene film obtained when the dripping speed of the aqueous phase solution in the composite nucleating agent microemulsion is too fast or too slow is slightly poor. This may be because the particle size and dispersibility of the oil-in-water microemulsion formed during the preparation of the microemulsion are adversely affected by the dripping speed.
[0232] By comparing Examples 1-5 with Comparative Example 7, it can be seen that when the surfactant in the composite nucleating agent microemulsion does not use the FC4430 of the present invention, the performance of the polyethylene film deteriorates. This may be because the fluorinated surfactant brings about a favorable effect on the dispersion performance of the microemulsion.
[0233] By comparing Examples 1-5 with Comparative Examples 8-10, it can be seen that when no composite nucleating agent microemulsion is added to the polyethylene composite material or only a single nucleating agent is added, various properties of the polyethylene film are greatly reduced. This may be due to the different dispersion degrees of the nucleating agent in the polyethylene composite material.
[0234] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention rather than to limit them. Although the embodiments of the present invention have been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the embodiments of the present invention can still be modified or replaced by equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A highly transparent, low haze polyethylene composite material, characterized in that: According to parts by weight, it includes the following components: Linear low density polyethylene LLDPE 100 parts Composite nucleating agent microemulsion 0.05-0.5 parts Antioxidant 0.1-0.3 parts Lubricant 0.1-0.5 parts; The composite nucleating agent microemulsion is a microemulsion obtained by compounding sodium benzoate and lithium bis(fluorosulfonyl)imide LiFSI; The preparation method of the composite nucleating agent microemulsion is: Sodium benzoate and lithium bis(fluorosulfonyl)imide are dissolved in deionized water and DMF respectively to obtain a sodium benzoate aqueous solution and a lithium bis(fluorosulfonyl)imide oil phase solution, a certain amount of surfactant is added to the lithium bis(fluorosulfonyl)imide oil phase solution and mixed evenly, then the sodium benzoate aqueous solution is added dropwise to the lithium bis(fluorosulfonyl)imide oil phase solution mixed with the surfactant within 30-50 seconds, and stirred and emulsified to obtain a composite nucleating agent microemulsion; The surfactant is a fluorinated polyester nonionic surfactant.
2. The high-transparency, low-haze polyethylene composite material according to claim 1, characterized in that: The mass ratio of sodium benzoate, lithium bis(fluorosulfonyl)imide and surfactant in the composite nucleating agent microemulsion is (3-5):1:(0.2-0.5); The mass concentration of sodium benzoate in the sodium benzoate aqueous solution is 10-20%; The mass concentration of lithium bis(fluorosulfonyl)imide in the lithium bis(fluorosulfonyl)imide oil phase solution is 5-15%.
3. The high-transparency, low-haze polyethylene composite material according to claim 1 or 2, characterized in that: The antioxidant is selected from one or more of antioxidant 1010, antioxidant 168 or antioxidant 1076; the lubricant is one or more of zinc stearate, calcium stearate or magnesium stearate.
4. A method for preparing the highly transparent, low haze polyethylene composite material according to any one of claims 1 to 3, characterized in that: The steps include: (1) Weigh the raw materials of each component according to the formula of claim 1, add them into a high-speed mixer, and mix at high speed for 10-15 minutes; (2) After the mixed raw materials are dried, they are added into a twin-screw extruder, and mixed and extruded at 160-220° C. to form granules to obtain a highly transparent and low-haze polyethylene composite material.
5. A highly transparent, low haze polyethylene film, characterized in that: The high-transparency, low-haze polyethylene composite material according to any one of claims 1 to 3 or the high-transparency, low-haze polyethylene composite material prepared according to claim 4 is prepared.
6. The high-transparency, low-haze polyethylene film according to claim 5, characterized in that: The specific preparation method of the high-transparency, low-haze polyethylene film is as follows: adding the high-transparency, low-haze polyethylene composite material into an extruder at 160-220° C., and obtaining a polyethylene film with a thickness of 30-50 μm after extrusion and casting.
7. Use of the high-transparency, low-haze polyethylene composite material according to any one of claims 1 to 3 or the high-transparency, low-haze polyethylene composite material prepared according to claim 4 in improving the transparency and haze of polyethylene films.